As imagens que o texto reflete: uma análise do éthos discursivo de Carolina Maria de Jesus em Quarto de despejo- diário de uma favelada - Flaviane Ferreira de Souza Batista (2024)
In this study, we analyze, in the light of French Discourse Analysis, Quarto de despejo: diário de uma favelada, by Carolina Maria de Jesus, to achieve the discursive ethos of the author (narrator and protagonist) in the mentioned book, without losing sight of the socio-political and ideological context in which she is inserted. In this way, we consider the Diary as a life story (Bertaux, 2005; Machado, 2016a, 2016b, 2020, 2021, among others) and we examine it through some plans of Maingueneau’s Global Semantics (2005), which are: the vocabulary, the themes, the enunciative deixis, and the enunciation mode. Based on such categories and on authors who study the notion of ethos, as, for instance, Amossy (2005), we seek to grasp the image(s) of herself that Carolina projects throughout her narrative, according to her “place of speech” and her physical and emotional state. The results point to the construction of several ethe (a psychosocial ethos, a political ethos, a writer’s ethos, the ethos of a [single] mother, ethos of a resident of Canindé community). These ethe overlap and articulate around a greater ethos: that of resilience, revealing a complex and multifaceted human being.